Naringenin promotes cell autophagy to improve high-fat-diet-induced atherosclerosis in ApoE-/- mice - Zhao,Ruifeng (2021)
Naringenin (NAR) is a major flavanone in citrus fruits that has multiple pharmacological attributes such as anticancer and antiatherogenic. This study aims to investigate the mechanism of NAR in high-fat-diet (HFD)-induced atherosclerosis (AS) in apolipoprotein E-knockout (ApoE-/-) mice. A HFD-induced AS ApoE-/- mouse model was established. The mice were treated with HFD, different doses of NAR and simvastatin (Simv). After drug treatment, the levels of total cholesterol (TC), triglyceride (TG), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), glutathione peroxidase (GSH-Px), malondialdehyde (MDA), superoxide dismutase (SOD), and alanine aminotransferase (ALT) were determined. The expression of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) was detected using qRT-PCR and enzyme-linked immunosorbent assay. The plaque area of the aorta of AS mice was determined using oil red O staining. Western blot analysis was applied to measure the levels of autophagy-related proteins [protein 1 light chain 3B (LC3B), beclin 1, and p62]. The TC, TG, LDL-C, TNF-α, ALT, and MDA levels were significantly increased while the HDL-C, SOD, and GSH-Px levels were decreased in the HFD-induced AS ApoE-/- mice. NAR treatment reversed the expression of the above indicators in mice. After they were treated with different doses of NAR, the LC3B and beclin 1 levels were improved while the p62 protein level was decreased. This study suggested that NAR could promote cell autophagy to improve HFD-induced AS in ApoE-/- mice.